Pengaruh Tipe Perusahaan, Ukuran Perusahaan dan Profitabilitas terhadap Laporan Keberlanjutan Interaktif (Studi Kasus PT Askrindo) - Oktavianty, Mufidah Sahla; Adelia Febriana; Maria Yovita R.Pandin (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This study aims to examine how the voluntary disclosure of interactive sustainability reporting is affected by the size, profitability, and type of credit companies listed on the Indonesia Stock Exchange between 2022 and 2023. This analysis uses secondary data, including sustainability reports and financial statements for fiscal years 2022-2023. PT Askrindo, which operates in insurance or other credit companies, is used as a benchmark for comparison in this report. The independent factors in this study are company type, company size, and profitability, with the natural logarithm of total assets for company size, return on assets (ROA) for profitability, and industry group classified as low profile and high profile as examples of independent variables. Sustainability reporting is the dependent variable used. This study uses a descriptive quantitative design and multiple linear regression models in data processing and analysis. The results of the multiple linear regression model show that company size does not affect sustainability reporting, but industry type and profitability have a significant effect.